Creative bracing: A descriptive overview of an alternative technique for non-operative fracture management of frail older adults. (November 2022) - Huyke-Hernández, Fernando A.; Only, Arthur J.; Leslie, Erin K.; Schroder, Lisa K.; Switzer, Julie A.
Abstract: As the world population ages, a higher proportion of older and frailer patients will sustain fragility fractures. Considering their depleted physiologic reserve and potentially different goals of care at their stage in life, these patients; especially those enrolled in hospice care, with profound dementia, or at end-of-life care; may not benefit from traditional surgical methods of fracture care. Non-operative treatment using standard immobilization or casting techniques in older and frailer patients can still render them susceptible to complications and adverse events. Here we describe our alternative non-operative treatment method of creative bracing to address the needs of this specific population. Creative bracing can be done with simple supplies available in almost all healthcare settings. Through patient-specific pre-treatment assessment, a creative brace tailored to the patient's risk factors and goals of care can be designed to provide sufficient fracture immobilization and comfort. Creative bracing is a low-cost, low-technical demand modality for non-operative treatment of some fragility fractures. Its benefit can be appreciated to greatest effect in the frailest patients for whom standard, surgical treatment does not represent best care.